The mechanism and pharmacodynamics of 2-((1H-indol-3-yl)thio/sulfinyl)-N-pheny acetamide derivative as a novel inhibitor against human respiratory syncytial virus. (31st December 2022) - Cheng, Ningning; Jiang, Nan; Fu, Yuanhui; Xu, Zhuxin; Peng, Xianglei; Yu, Jiemei; Cen, Shan; Wang, Yucheng; Zhang, Guoning; Zheng, Yanpeng; He, Jinsheng
Abstract: Human respiratory syncytial virus (RSV) is a leading cause of lower respiratory tract infection worldwide. Until now, there are no licenced vaccines or effective antiviral drugs against RSV infections. In our previous work, we found 2-((1H-indol-3-yl)thio/sulfinyl)-N-pheny acetamide derivatives (4-49 C and 1-HB-63) being a novel inhibitor against RSV in vitro . Here, we explored the underlying mechanism of 2-((1H-indol-3-yl)thio/sulfinyl)-N-pheny acetamide derivatives to inhibit RSV replication in vitro and disclosed that 4–49 C worked as the inhibitor of membrane fusion and 1-HB-63 functioned at the stage of RSV genome replication/transcription. Yet, both of them could not inhibit RSV infection of BALB/c mice by using RSV-Luc, in vivo imaging and RT-qPCR analyses, for which it may be due to the fast metabolism in vivo . Our work suggests that further structural modification and optimisation of 2-((1H-indol-3-yl) thio/sulfinyl)-N-pheny acetamide derivative are needed to obtain drug candidates with effective anti-RSV activities in vivo . Graphical Abstract: UF0001